EVALUASI BUDAYA ORGANISASI DALAM MENDUKUNG OPERASIONAL SISTEM E-GOVERNMENT PEMERINTAH PROVINS! SUMATERA SELATAN - Isnawijayani Isnawijayani (Jurnal Masyarakat Telematika dan Informasi, 2010)
Assessment of Organizational Culture on Supporting Operational Systems in £-government program of South Sumatra provincial government, aims to find out how the e-government implementation process, the factors supporting and inhibiting as well as to identify policy measures and what needs to be done to overcome barriers to develop and implementing egovernment in South Sumatra provincial government. Studies conducted in the Communications and Information Agency of South Sumatra province by using qualitative descriptive analysis technique with evaluative method. Summative evaluation is chosen because the evaluation is done after the development and implementation of the egovernment program. Meanwhile, according to Bogdan and Taylor (2000:3) that qualitative methodology is a research procedure that produces descriptive data in the form of words written or spoken of the people and observed behavior. By using the measurement of qualitative data, researchers are expected to study the deep social phenomena that occur, in terms of e-government it is expected to give an idea about development and implementation in the Government of South Sumatra Province. From the research we can found that: (1) The development of e-government program in South Sumatra provincial government does not meet the goals and objectives that have been planned. (2) Rejection of the new work culture, job transition from manual to digital. (3). Lacking in human resources in the area of Information Technology, training should be done continuously. (4) The need to make a policy that urges the application of e-government from senior levels down to the regular employee.